An Analysis of Pronunciation Errors in The Production of Silent Letters of English Language by Secondary School Students in Borno State - Musa Abubakar (Emerging Trends in Languages, 2025)
Perfect pronunciation as one of the effective language skills in communication greatly affects teaching, learning and usage of English as a second language because it enhances transfer of information from source to target. This paper adopted Corder explanation of errors and mistakes which sees them as gaps/deficiencies in learners’ knowledge of a language as theoretical framework and analysed pronunciation errors of the English silent letters by Senior Secondary School students of five schools in Biu, Kwaya-Kusar, Hawul, Bayo and Shani Local Government Areas of Borno State Nigeria via purposeful sample of ten (10) students. The data were collected through reading task: twenty sentences containing words with the selected silent letters. The results show dominant pre-systemic errors with a total number of one-hundred and sixty (160) errors from two hundred (200) pronunciation exercises. The study emphasizes how learners' competence is affected by a lack of phonological awareness and suggests specific pedagogical approaches to correct these mistakes, such as more teacher training, phonetic drills, and frequent assessments. Pronunciation can also be enhanced by creating an atmosphere where students are encouraged to practice speaking English aloud. This study enhances the teaching and learning of English pronunciation, especially in multilingual situations like Nigeria, by highlighting the significance of silent letters in the language and offering precise instructions.
Keywords: English language; Pronunciation; errors; secondary school; silent letters